Challenges and Solution of Invasive Aspergillosis in Non-neutropenic Patients: A Review - Bassetti, Matteo (Infect Dis Ther, 2017)
Invasive aspergillosis (IA) is a serious opportunistic infection, which has increasingly been recognized as an emerging disease of non-neutropenic patients. In this group of patients, the diagnosis of IA can be challenging owing to the lack of specificity of symptoms, the difficulty in discriminating colonization from infection, and the lower sensitivity of microbiological and radiological tests compared with immunocompromised patients. The aim of this article is to present to clinicians a critical review on the management of IA in non-neutropenic patients.